Design for environment analyses applied to rapid manufacturing - Hopkinson, N; Gao, Y; McAfee, D J (Proceedings of the Institution of Mechanical Engineers. Part D, Journal of automobile engineering, 2006)
Abstract This paper explores the potential to combine rapid manufacturing (RM) technologies and design for environment (DFE) software with an automotive application. The work focuses on the redesign of a door handle assembly for the Jaguar XJ Saloon. The original 11-piece assembly, comprising eight different materials, was subject to a redesign with an RM technology in mind as the method for final manufacture. In this case the suggested method for manufacture was selective laser sintering (SLS). The design freedoms afforded by the SLS process had a profound effect on the potential to redesign the product. Two different redesigns were proposed, and these, along with the original design, were subjected to analyses of environmental burden and financial profits/costs for end-of-life recycling and reuse using Boothroyd Dewhurst DFE software. The first redesign incorporated the entire assembly as a single prefabricated unit and consequently rendered a DFE analysis impossible. The second redesign was a four-piece assembly retaining three metallic components from the original product and, when subjected to the DFE analysis, showed a significant reduction in environmental burden and cost for disassembly. The surface finish of the SLS parts proved to be inadequate for visual components on a luxury car, but the potential to apply RM for applications with less stringent aesthetic requirements remains.